Juridical Analysis of MSME-Based Startups regarding the Legality of Business Operations by Semarang State Polytechnic Students - Malebra, Irawan -; Rini, Nur -; Paniyah, Paniyah -; Farouk, Umar -; Devie, Erika - (Politeknik Negeri Semarang, 2024)
Micro, Small, and Medium Enterprises, hereinafter referred to as MSMEs, are startups whose growth is being promoted in Indonesia. This study aims to analyse the awareness of the importance of legal business operations for MSME-based startups. Based on the Presidential Regulation of the Republic of Indonesia Number 98 of 2014 concerning Licensing for Micro and Small Businesses Article 1 Paragraph 3, a micro and small business permit, hereinafter abbreviated as IUMK, is a sign of legality to a person or business actor / certain activities in the form of a micro and small business permit in the form of one sheet. This permit certainly has an important role in supporting the running of related MSMEs. This research was conducted on 29 Independent Entrepreneurial Students of Politeknik Negeri Semarang. Respondents consisted of 65.5% women and 34.5% men. The majority of business types, 82.8%, are businesses in the culinary field. In this study, 62.1% of respondents considered that business legality was important for the business they were running. However, 72.4% of the respondents admitted that they had not taken care of their business legality. This business legality has not been taken care of for several reasons, the majority of which are because business legality management seems time-consuming, costly, and difficult to do. It can be concluded that the awareness of MSME actors, in this case, POLINES Independent Entrepreneurial Students, regarding the importance of business legality is high, it is just that it is necessary to update the procedures for obtaining business legality which is easier to do. In addition, there is a need for socialisation and assistance by the government, practitioners, and lecturers who work together to not only expand awareness of the importance of micro, small and medium enterprises legality but also provide knowledge on how to take care of MSME legality